2020
DOI: 10.21203/rs.3.rs-73448/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Intravenous Immunoglobulin on the Course of Severe COVID-19: Results From a Retrospective Data Analysis of a Patient Cohort in Turkey Treated With or Without Octagam®

Abstract: Background: There is some evidence from case reports and a few studies in China that critically ill COVID-19 patients may benefit from treatment with intravenous immunoglobulins (IVIG). We compared clinical outcomes and biomarkers in a Turkish cohort of patients with severe COVID-19 who were treated with the institution's standard of care (SOC), either alone or in combination with IVIG.Methods: Data from COVID-19 patients treated in two intensive care units at the University hospital of Istanbul was analyzed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…**Only in survivors at day 90. consistent with the main result and did not show any beneficial effect of IVIG (figure 3; appendix 1 p 18). A posthoc analysis of mortality showed no statistically significant interaction between the IVIG and corti costeroid administration or body-mass index for the unadjusted mortality odds ratios at day 28 and day 90 (appendix 1 pp 18,[31][32]. The sensitivity analysis done on the per-protocol population for both the primary outcome and competing events confirmed the non-significant treatment effect shown by the intention-to-treat analysis (appendix 1 p 19).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…**Only in survivors at day 90. consistent with the main result and did not show any beneficial effect of IVIG (figure 3; appendix 1 p 18). A posthoc analysis of mortality showed no statistically significant interaction between the IVIG and corti costeroid administration or body-mass index for the unadjusted mortality odds ratios at day 28 and day 90 (appendix 1 pp 18,[31][32]. The sensitivity analysis done on the per-protocol population for both the primary outcome and competing events confirmed the non-significant treatment effect shown by the intention-to-treat analysis (appendix 1 p 19).…”
Section: Resultsmentioning
confidence: 70%
“…14 Retrospective observational studies have suggested that IVIG decrease mortality and duration of invasive mechanical ventilation in COVID-19-associated ARDS. [15][16][17][18][19] Further more, it has been reported in China that about a third of patients with COVID-19 and ARDS have been treated with IVIG, without the specific effect of IVIG being evaluated. [20][21][22] However, because of the cost and scarcity of IVIGs, which is currently indicated in various autoimmune and inflammatory diseases, showing the efficacy and safety of IVIG in patients who are critically ill with COVID-19 is needed to explore IVIG therapy as a viable treatment option.…”
Section: Introductionmentioning
confidence: 99%